Why do firms compete on price comparison websites? The impact on productivity, profits, and wages - Charlie Lindgren; Yujiao Li; Niklas Rudholm (Institute of Retail Economics (HFI), 2020)
This paper investigates how firm entry into a price comparison website marketplace affects firm productivity, profits, and wages. We want to answer the key research question: Why do firms compete on price comparison websites? A substantial literature indicates that competition in such marketplaces is fierce, leading to lower prices for products sold. We suggest that participation in these marketplaces also leads to increased productivity, i.e., output increases when holding constant the level of inputs used. This leads to increased profits, motivating firms to enter price comparison websites despite fierce competition. Our results indicate that for the full sample of firms, PriceSpy participation increases output by almost 12% when holding the level of inputs constant. Also, investigation of who gains from the increased productivity shows that, for entering firms, operating profits increase by 9% and gross wages by 14% when studying the full sample of firms. That labor gains more from PriceSpy participation is even clearer when studying the impact on wholesale and retail firms separately. For those firms, gross wages increased by 16–17% after entry, while no statistically significant impact was found regarding operating profits.
Keywords: D22; D24; D33; L81; 330; Online retailing; e-commerce; price comparison websites; productivity; value added